Dinamika Kolaborasi Dalam Pengembangan Wisata Candi Gedongsongo Kabupaten Semarang - Wiwid Fitriani; Retno Sunu Astuti (Universitas Muhammadiyah Ponorogo, 2026)
Gedongsongo Temple is a multi-actor tourism site (involving Government, MCB, Perhutani, Private Sector, and Community) that requires sustainable development to effectively balance economic priorities with cultural and environmental preservation. This qualitative descriptive study utilizes the Collaborative Governance Regime (CGR) theory (Emerson & Nabatchi, 2015) and the Government of Canada's framework to analyze the collaborative dynamics and their hindering factors. Findings conclude that collaboration is suboptimal, characterized by the persistent pull-and-push of competing interests. Specifically, Principled Engagement faces structural imbalance, Shared Motivation is fragile and pragmatic due to emerging trust issues, and Capacity for Joint Action is constrained by deviance and suboptimal knowledge/resource management. The identified inhibiting factors are rooted in cultural, institutional, and political aspects. The study ultimately concludes that the dynamics remain structurally weak, primarily due to asymmetric power relations and a profound lack of trust, failing to fully optimize the sustainable development goals. Keywords: Temple; Multi-actor; Tourism;